Let's define the following variable.
x = first integer
y = second integer
If the sum of their squares is 34, then we can form the equation below:
![x^2+y^2=34](https://img.qammunity.org/2023/formulas/mathematics/high-school/8qpy8jcc3tp3j1t836h3nfq9v13snc76mg.png)
If the other integer, say x, is 1 less than twice the other (y), then we can form this second equation:
![x=2y-1](https://img.qammunity.org/2023/formulas/mathematics/college/dhkm269roe93ipg2im3tphy7m881fxhzk8.png)
From these two equations, we can now solve for the values of x and y.
Here are the steps.
1. Replace the value of "x" in equation 1 using the value in equation 2.
![(2y-1)^2+y^2=34](https://img.qammunity.org/2023/formulas/mathematics/college/e6ma5w38cb9c7qfi72z67u78n4pntawkpq.png)
2. Apply the exponent.
![\begin{gathered} (4y^2-4y+1)+y^2=34 \\ 4y^2-4y+1+y^2=34 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3zmkvfnohffuoa28pr47wdyzz3xaqfwh1l.png)
3. Rearrange the terms. Subtract 34 on both sides of the equation then, combine similar terms.
![\begin{gathered} 4y^2+y^2-4y+1=34 \\ 4y^2+y^2-4y+1-34=34-34 \\ 5y^2-4y-33=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ljvhfnx5qab6zvjmwg72q8g1ckuqk60l3v.png)
In step3, we are able to create a quadratic equation in a standard form that is ax² + bx + c wherein a = 5, b = -4, and c = -33.
To solve for the value of y, we can use the Quadratic formula.
![y=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/gfo69urp8rw17yg122uzk6md9epfe1uf75.png)
Since we have already determined the values of a, b, and c, let's plug them into the formula above.
![y=\frac{-(-4)\pm\sqrt[]{(-4)^2-4(5)(-33)}_{}}{2(5)}](https://img.qammunity.org/2023/formulas/mathematics/college/ieti41t21t27cocnxpxa671nz7vpwxfpi4.png)
Then, solve for y.
![\begin{gathered} y=\frac{4\pm\sqrt[]{16+660}}{10} \\ y=\frac{4\pm\sqrt[]{676}}{10} \\ y=(4\pm26)/(10) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fruijyau5s4274t0djvyv9b0fhjrik75ku.png)
Separate the plus and minus signs.
![\begin{gathered} y=(4+26)/(10)=(30)/(10)=3 \\ y=(4-26)/(10)=-(22)/(10)=-2.2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1rap1s7d20j70wu8lsq8bmp59aiwcdq4tm.png)
There are two possible values y but only one is an integer. So, we will use y = 3.
To solve for the other integer x, let's use the second equation plugin y = 3.
![\begin{gathered} x=2y-1 \\ x=2(3)-1 \\ x=6-1 \\ x=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/srj739uhwcy4irbpqgx8zq9j7f6k6qkna1.png)
Therefore, the integers are 5 and 3.